TRAITEMENT DES MARGINES PAR UN PROCEDE COUPLANT LA COAGULATION FLOCULATION ET LA VOIE ELECTROCHIMIQUE - Sbai, G.; Loukili, M. (European Scientific Journal, ESJ, 2015)
The purpose of this study is the treatment of olive wastewaters by the combination of two physicochemical processes: the coagulation, flocculation as pre-treatment and a treatment by electrochemical way as the process of refining. Olive wastewaters presented a chemical oxygen demand (COD) of 32,71 g of O2/l, an acid pH (5,02), and a dissolved oxygen of 0,5 mg/l and a concentration of polyphenols of 1,22 g/L. The tests of coagulation were realized by means of the bench of jar-test, established by a series of six flasks subjected to increasing doses of the coagulant (the sulfate of aluminium). The tests allow to eliminate 42% of the COD, 58% of suspended matter (SM), 22% of polyphenols, 83% of turbidity, and 42% of the coloring. The effluent pre-processed by coagulation, flocculation, which has an optimum dose of sulfate of aluminium, undergoes to filtration then handled by an electrochemical reactor; where the intensity in 5A, the tension 14V, the temperature 30°C, the speed of agitation 200 tr/min, and the salinity in 0,5 g/l. This electrochemical treatment allowed to reduce the color intensity by 86%, the COD by 30%, the polyphenols by 57% and the turbidity by 41%. It emerges from all the results that the treatment by coupling coagulation, flocculation and electrochemical processes allowed reach a COD of 9,11g d’O2/L, a SM of 0mg/L, a solved oxygen of 7,16 mg/L and a concentration of Polyphenols of 0,32 g/L.